Robotic Arm Using Servo Motor and Arduino Uno Controlled with Potentiometer - Shulhan Shulhan; Farhan Astwensa; Fikrie Reza Fauzan; Iksan Bukhori (Journal of Electrical And Electronics Engineering, 2021)
Robotic arm has been widely used in many applications, especially in industry. With this kind of advancement, the needs to introduce this technology to students at early age has increased. However, many students still consider this kind of technology as something out of reach. This project aims to create a very simple robotic arm using servo motor and materials which can be easily obtained around the household. The resulting robot is also programmable and electronically movable, thus enabling more freedom of how to move it. This in turn create a good introductory tool for the students to learn about the structure and motion of robotic arm.